2013
DOI: 10.1007/s00586-013-2749-x
|View full text |Cite
|
Sign up to set email alerts
|

MRI features of the psoas major muscle in patients with low back pain

Abstract: Purpose The purpose was to investigate the changes of the psoas major muscles (PM) cross-sectional area (CSA) and fat infiltration in the PM and to investigate the association between the morphology of the PM and expression of the degenerative changes of lumbar spine in patients with low back pain (LBP). Methods T2-weighted scans for measurements of the CSA and analysis of fat infiltration were performed on 42 patients and 49 controls using a 1.5 Tesla MR system. For a quantitative analysis of fat tissue infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 24 publications
1
64
1
1
Order By: Relevance
“…17 In the present study, there was significantly more fat infiltration in patients with CLBP than in asymptomatic volunteers, as assessed using conventional T 2 weighted transverse images; this finding is consistent with the results of previous reports. 17,26 Moreover, in this study, adipose tissue was distinguished from IMCL and EMCL as fat content in the Pm and Mm, whereas previous studies reported the increased fat content as total amount of adipose tissue in the Mm of patients with CLBP. Increased IMCL content in skeletal muscles has been associated with obesity 27,28 and ageing.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…17 In the present study, there was significantly more fat infiltration in patients with CLBP than in asymptomatic volunteers, as assessed using conventional T 2 weighted transverse images; this finding is consistent with the results of previous reports. 17,26 Moreover, in this study, adipose tissue was distinguished from IMCL and EMCL as fat content in the Pm and Mm, whereas previous studies reported the increased fat content as total amount of adipose tissue in the Mm of patients with CLBP. Increased IMCL content in skeletal muscles has been associated with obesity 27,28 and ageing.…”
Section: Discussioncontrasting
confidence: 54%
“…32,36,37 Lost muscle strength is associated with the accumulation of EMCL, which can interfere with sufficient muscle nutrition. [36][37][38] With regard to fat degeneration in the Pm, some studies 24,26 have reported that the Pm of other examinees showed minimal fat degeneration. In the present study, no significant difference was found in the fat degeneration in the Pm between patients with CLBP and controls.…”
Section: Discussionmentioning
confidence: 97%
“…10 However, various cross-sectional studies have reported PSM atrophy in LBP. 2,9 While the deleterious influence of advancing age on the PSM area was demonstrated in our study as well, there was an unexpected predisposition for the female sex to have smaller psoas muscle area values. While the MF muscle has been reported to be particularly indicative of localized disc or root pathology, 3 atrophy of this and other muscles (ES, quadratus lumborum, and psoas) has not demonstrated any correlation with symptom duration or pain scores in previous studies.…”
Section: Lumbar Psm Morphometry and Its Correlationsmentioning
confidence: 75%
“…Magnetic resonance imaging (MRI) is frequently used to quantify and determine any association between muscle morphology and neuromusculoskeletal pathology or dysfunction through the evaluation of muscle cross-sectional area (CSA) (1,2,3,4,5,6,7) and muscle fatty infiltrate (MFI) (5,8,9,10,11,12). These parameters of muscle morphology are also often investigated to identify expected age-related muscle changes (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…
IntroductionMagnetic resonance imaging (MRI) is frequently used to quantify and determine any association between muscle morphology and neuromusculoskeletal pathology or dysfunction through the evaluation of muscle cross-sectional area (CSA) (1,2,3,4,5,6,7) and muscle fatty infiltrate (MFI) (5,8,9,10,11,12). These parameters of muscle morphology are also often investigated to identify expected age-related muscle changes (13,14).

Many, though not all, studies analysing spinal muscle CSA and MFI report intra-and/or inter-rater reliability as part of their investigations (4,5,7,15,16), many of which demonstrate strong intra-rater reliability of lumbar erector spinae and multifidus CSA, with an intraclass correlation (ICC) ranging from 0.85 (5, 15) to 0.98 (4) and an inter-rater reliability ranging from 0.77 (7) to 0.85 (5).

…”
mentioning
confidence: 99%